2012
DOI: 10.1111/micc.12000
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Intercellular Ca2+ Signaling in Endothelial Cell Tubes of Mouse Resistance Arteries

Abstract: Objective To test the hypothesis that Ca2+ responses to G-protein coupled receptor (GPCR) activation are coordinated between neighboring endothelial cells of resistance arteries. Methods Endothelial cell tubes were freshly isolated from superior epigastric arteries of C57BL/6 mice. Intercellular coupling was tested using microinjection of propidium iodide. Following loading with fluo-4 dye, intracellular Ca2+ responses to ACh were imaged with confocal microscopy. Results Cell-to-cell transfer of propidium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 59 publications
2
52
0
Order By: Relevance
“…The SEA is dissected free from surrounding skeletal muscle fibers and connective tissue, blood is flushed from the lumen, and mild enzymatic digestion is performed to enable removal of adventitia, nerves and smooth muscle cells using gentle trituration. These freshly-isolated preparations of intact endothelium retain their native morphology, with individual ECs remaining functionally coupled to one another, able to transfer chemical and electrical signals intercellularly through gap junctions 6,7 . In addition to providing new insight into calcium signaling and membrane biophysics, these preparations enable molecular studies of gene expression and protein localization within native microvascular endothelium.…”
mentioning
confidence: 99%
“…The SEA is dissected free from surrounding skeletal muscle fibers and connective tissue, blood is flushed from the lumen, and mild enzymatic digestion is performed to enable removal of adventitia, nerves and smooth muscle cells using gentle trituration. These freshly-isolated preparations of intact endothelium retain their native morphology, with individual ECs remaining functionally coupled to one another, able to transfer chemical and electrical signals intercellularly through gap junctions 6,7 . In addition to providing new insight into calcium signaling and membrane biophysics, these preparations enable molecular studies of gene expression and protein localization within native microvascular endothelium.…”
mentioning
confidence: 99%
“…The physiological significance of Ca 2+ waves is still unclear however it has been suggested that oscillatory Ca wave signaling in the EC can regulate vasomotor tone (Socha et al 2012) however the exact physiological roles of individual signaling mechanisms still need to be discerned.…”
Section: Discussionmentioning
confidence: 99%
“…Agonist-induced oscillatory Ca 2+ waves have been observed in both the SMCs Iino, Kasai, and Yamazawa 1994;Boittin et al 1999;Jaggar and Nelson 2000;Dai et al 2007;Dai et al 2006;Lee et al 2001;Syyong et al 2009) and ECs (Beliveau, Lapointe, and Guillemette 2011;Socha et al 2012) (Keener and Sneyd 1998). In another scenario, the whole cell is oscillatory, and spatial cellular heterogeneity can cause the wave like pattern appearance due to phase differences in oscillatory activity in different region of the cells (Jafri and Keizer 1994).…”
Section: If the Localized Camentioning
confidence: 99%
See 2 more Smart Citations